Organic farming increases functional diversity and ecosystem service provision of spontaneous vegetation in Mediterranean vineyards. (March 2023) - Rotchés-Ribalta, Roser; Marull, Joan; Pino, Joan
Highlights: Spontaneous plant species represent key ecological indicators of vineyard management. Via plant functional response-effect frame, management impacts pollination services. Organic farming held more diverse plant community and varied competitive strategies. Organic farming held diverse and resilient communities for pollinator provisioning. Abstract: Spontaneous plant species in agricultural systems (i.e., weeds) are bound to become key ecological indicators of agroecosystem resilience as they show high sensitivity to management, while they ensure the assembly of multiple ecological functions. Here we used the response-effect functional framework on spontaneous plant species growing in both organic and conventional vineyards, to assess whether their plant communities respond to contrasted farming systems and to soil conditions according to its competitive response and the provisioning of pollination services. The results show that the spontaneous plant communities and its functions better reflected the effects of management -when considering the dichotomy organic-conventional farming- rather than soil conditions. Organic management in vineyards promoted higher plant species richness, with varied competitive response strategies to deal with different environmental conditions and management disturbances. Organic vineyards held more diverse and resilient plant communities for the provisioning of pollinator services than the conventional ones, which is expected to enhance pollinator communities with diverse feeding guilds. In contrast, conventional farming systems selected anemophilous plants or those with flower attributes related to generalist pollinators. Such results highlight the significance of organic farming for the sustainment of the local accompanying plant diversity but also for the provisioning of ecosystem services in these agricultural landscapes. Besides, the study reinforces the applicability of the response-effect framework to identify the effects of vineyard management on the spontaneous plant communities and its potential impacts on the pollinator communities.